2014
DOI: 10.1016/j.jsps.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitude toward use of over the counter medicines during exams in Saudi Arabia

Abstract: The use of OTC medication during exams was more among high school and university students. Gender, age and educational institution were found significantly affecting the use of OTC medicines during exams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 11 publications
8
52
2
3
Order By: Relevance
“…The finding of women using more OTC drugs than men was in line with previous research findings from Germany [7,8] as well as from other countries [19][20][21][22][23]. Women's higher use of analgesics can partially be explained by different pain perception and menstrual pain [24].…”
Section: Discussionsupporting
confidence: 89%
“…The finding of women using more OTC drugs than men was in line with previous research findings from Germany [7,8] as well as from other countries [19][20][21][22][23]. Women's higher use of analgesics can partially be explained by different pain perception and menstrual pain [24].…”
Section: Discussionsupporting
confidence: 89%
“…[10,20,21] Our findings generally revealed no significant difference in use of analgesics between male and female as the previous study in Iran and that converse to other studies in Riyadh, Taif, turkey, Germany, and Norway. [1,14,15,17,22,23] Like our findings in Saudi, many studies have also shown there is a significant age difference in the prevalence of analgesic use among the population. Studies conducted in Taif, Sweden, United States, and Norway have shown an association between age and analgesic use.…”
Section: Discussionsupporting
confidence: 81%
“…The strengths include the use of a large area of the general population; it is not limited to the specific cities or level of education like other studies. [10,22,23,30,31] On the other hand, the electronically distributed questionnaire gave a great opportunity to the young female to take part in the study. Furthermore, higher education was predominating among electronically recruited individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among high school students in Riyadh city reported a nominal consumption of caffeine in the form of energy drinks (5 %) during exams. This finding implied that consumption of caffeine has increased a lot among higher secondary students during examination period which is one of the stressor [18].…”
Section: Discussionmentioning
confidence: 91%